Investigation of Friedel-Crafts Alkylation in the Presence of Supported Sulfonic Acid on Silica Gel - A. R. Kiasat; M. Karimi-Cheshmeali; R. Soleymani; H. Rajabzadeh (E-Journal of Chemistry)
From the Reaction between cellulose and chloro sulfonic acid was prepared sulfuric acid cellulose composition as a new solid acid. The solid acid supported on silica gel and then as an effective catalyst in Friedel-Crafts alkylation of alcohols and aromatic compounds was used. The reaction progress was controlled using thin layer chromatography and the reaction products were analyzed using IR spectroscopy devise. The results show this new catalyst is effective in the friedel crafts alkylation and C-C bond formation was done in short time with very good yields.